FINANCIAL ANALYSIS OF PT PELAYARAN NASIONAL SRIANDALAS INDAH MURNI: COMMON SIZE & PROFITABILITY RATIOS - Alamsyahbana, Muhammad Isa; Wiwin Vartina; Ranti Utami; Sri Kurnia; Juliani Sari Siregar (Universitas La Tansa Mashiro, 2024)
This study analyzes the financial performance of PT Pelayaran Nasional Sriandalas Indah Murni-Kota Tanjungpinang using the common size method and financial ratios. Data was collected through documentation and literature study. The common size analysis results show an increase in capital and a decrease in debt for 2019-2020 and 2020-2021. The income statement for 2019-2020 indicates improved performance with reduced costs and increased profits, whereas 2020-2021 shows a decline in performance due to increased costs and decreased profits. Financial ratio analysis for 2019-2021 reveals a significant amount of unproductive working capital in cash and receivables, resulting in suboptimal asset funding. The high equity guarantee comes from long-term liabilities. In conclusion, financial performance improved in the balance sheets for 2019-2020 and 2020-2021 but declined in the income statement for 2020-2021. The financial ratios indicate unproductive working capital and high equity guarantees from long-term liabilities